A sustainable NEV manufacturer-retailer system under the Nash bargaining framework: considering the impact of the COVID-19 epidemic under the CVaR criterion - Han, Shifeng; Cheng, Yijie (Frontiers in Energy Research, 2023)
Suppose a new energy vehicle (NEV) manufacturer-retailer system where the wholesale price and the order quantity are determined through a negotiation procedure. Considering the impact of the COVID-19 epidemic, the manufacturer and the retailer are both assumed to be risk averse with Conditional Value-at-Risk (CVaR) as their performance measure. With the uniform distribution assumption, we derive the equilibrium solutions as well as the players’ profit shares in the Stackelberg game and Nash bargaining framework. We quantitatively address the impacts of the players’ confidence levels and government subsidy on the equilibrium order quantity, wholesale price and profit allocation in both negotiation frameworks. We find that, in both negotiation frameworks and considering the impact of the COVID-19 epidemic, a more risk-averse (i.e., with lower confidence level in CVaR model) manufacturer or retailer tends to occupy a higher profit share. On the other hand, a higher government subsidy aiming at offsetting the epidemic’s impact leads to a higher profit share for the manufacturer and a lower one for the retailer. A quantitive comparison of the equilibriums in the two negotiation frameworks indicates that more NEVs are ordered by the retailer and a higher system profit is generated in the Nash bargaining framework than the Stackelberg game. Thus, we analytically prove that the Nash bargaining framework is superior to the Stackelberg game for the NEV manufacturer-retailer system in terms of both quantity and profit with consideration of the epidemic impact. In addition, a series of numerical experiments is carried out to illustrate the effects of some significant parameters on the equilibrium order quantity and the system profit allocation in different negotiation frameworks. These numerical experiments also further demonstrate the superiority of the Nash bargaining framework for either NEV player—no matter how the epidemic trend and the government subsidy vary—and provide a quantitative scope for the retailer’s bargaining power to sustainably maintain the win-win cooperation between the NEV manufacturer and retailer in the superior Nash bargaining framework within the epidemic environment. From the perspective of policy, the government should increase subsidy within the epidemic environment to offset the negative effect and can degenerate subsidy when the epidemic dissipates. Furthermore, as the subsidy degenerates, both model results and numerical experiments show that the manufacturer suffers a more unfavorable effect, so the government can preferentially support the manufacturer by adjusting the subsidy to a higher level to alter players’ relative powers and profit shares.